2010
DOI: 10.1007/s00268-009-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Extracapsular Invasion of Sentinel Lymph Nodes in Breast Cancer: Prediction of Nonsentinel Lymph Node Metastasis

Abstract: Our results suggest that the presence of ECI at metastatic SLNs is a strong predictor for residual disease in the axilla. These findings imply the possibility that ALND might be foregone in the treatment of patients with breast cancer without ECI at metastatic SLNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Capsular invasion at metastatic nodes in breast cancer was shown to be strongly associated with further regional nodes metastasis [37,38]. Thus, such a possible increased risk may be related to breast cancer progression, specifically in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular invasion at metastatic nodes in breast cancer was shown to be strongly associated with further regional nodes metastasis [37,38]. Thus, such a possible increased risk may be related to breast cancer progression, specifically in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The disease stage at diagnosis is widely recognized as one of the most important prognostic factors in patients with breast cancer. Traditionally, the pathological determination of tumor size and lymph node status have guided prognosis and adjuvant therapy recommendations for patients with breast cancer (1)(2)(3). Several biomarkers, including endocrine hormone receptor status and human epidermal growth factor receptor 2 (HER2) status, have recently been added to risk evaluation and therapeutic assessment (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…1214 In our previous study, the presence of an ECI at SLNs was found to be a strong predictor of residual axillary disease, or NSLN metastasis. 15 Thus, this study was undertaken to evaluate the presence of ECI in positive SLNs as a predictor of disease recurrence in breast cancer. The key observations made in this study can be summarized as follows: In our metastatic SLN cases, the number of positive lymph nodes and primary tumor size were significantly associated with the recurrence, but the presence of an ECI at SLNs was not a predictor of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 ECI was defined as extra capsular growth of tumor cells, invasion of perinodal fat or extranodal location of tumor cells. 15 Fisher's exact test, the χ 2 test, and Student's t test were used to compare recurrent and nonrecurrent groups. Multivariate analysis was performed with logistic regression analysis to select covariates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation